Kepribadian Serakah (Greed) sebagai Tantangan Etika dan Kepemimpinan dalam Profesi Akuntan Manajemen - Nurul Fitriani; Adib Minanurohman; Gery Lusiano Firmansah (Jurnal Bisnis dan Akuntansi, 2022)
This study examines the greedy personality as an ethical leadership challenge in the management accounting profession. This topic is important due to top level management accountants serve as a leader and carry out their responsibility to society and association through code of ethics and ethical leadership. The discussion results show that management accountants with greedy personalities are more susceptible to fraud, which violates management accountants code of ethics such as integrity, objectivity, and professional behavior. In addition, ethical leadership values that have the potential to be violated because of greedy personality are sincerity, integrity, trustworthiness, wise in decision making, and empathy for others. Finally, this article proposes a solution that can use to reduce the impact of a greedy personality in a management accountant through (1) held social awareness program that involves all elements of the company including top level accountant management (2) supportive environment, culture, and policies from company (3) improving faith through spiritual program.